Digital System Model for Asset Management in the Universities in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The  article   was conducted to develop and to evaluate digital system model  for asset management in the universities in thai supply chain. A samples group in the research study consisted of ten  experts consisted of five experts on supply chain management, five experts on digital, Data were analysed by arithmetic mean and standard deviation. The article findings model six elements namely main components, Suppliers , Universities , customers,  satisfaction, feedback . The assessment digital system model  for asset management in the universities in thai supply chain using Black-Box technique and The results from experts agreement digital system model  for asset management in the universities in thai supply chain was a high level. The model could be used to develop digital asset in the universities.